Simultaneous determination of glipizide and its four hydroxylated metabolites in human urine using LC–MS/MS and its application in urinary phenotype study - Tan, Bo; Yang, Aidong; Yuan, Weian; Li, Yue; Jiang, Lei; Jiang, Jian; Qiu, Furong (Journal of pharmaceutical and biomedical analysis, 2017)
•LC–MS/MS method was developed and validated for determination of glipizide and its four metabolites in human urine.•The method was successfully applied to urinary study in healthy volunteers.•For the first time, 4-cis-OH-gp and 3-trans-OH-gp were found and identified in the study. Cytochrome P450 (CYP) 2C9 and CYP2C19 genetic mutant could influence the plasma concentration of glipizide in human subjects, which refers to glipizide safety and adverse effects in clinic practice. A further study to investigate the relationship of the concentrations between glipizide and its metabolites in human with different CYP mutants was valuable. We firstly develop a validated liquid chromatography–tandem mass spectrometry (LC–MS/MS) method for simultaneous quantification of glipizide and its hydroxylated metabolites in human urine. After simple protein precipitation with methanol including 4′-OH-tolbutamide and gliclazide (both are internal standards), the analytes were chromatographed on a reversed-phased column with a mobile phase of 0.1% formic acid in acetonitrile and 0.1% formic acid in water by a gradient elution. The ion transitions of the precursor to the product ion were principally protonated ions [M+H]+ at m/z 446.4→m/z 321.1 for glipizide, m/z 462.2→m/z 321.1 for the four hydroxylated forms of glipizide, m/z 287.2→m/z 188.0 for 4′-OH-tolbutamide, and m/z 324.1→m/z 127.1 for gliclazide. The method was linear over a concentration range of 0.02–20.0ng/mL. The intraday and inter-day variances were less than 9.9%, and accuracy was within ±6.8%. The method was successfully applied to the urinary phenotyping study in volunteers after a single oral administration of 5-mg glipizide tablet, and two new hydroxycyclohexyl metabolites of glipizide (OH-gp), 4-cis-OH-gp and 3-trans-OH-gp, were found in this study.